2014
DOI: 10.1016/j.scitotenv.2013.08.080
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of impact of shale gas operations in the Barnett Shale region on volatile organic compounds in air and potential human health risks

Abstract: Shale gas exploration and production (E&P) has experienced substantial growth across the U.S. over the last decade. The Barnett Shale, in north-central Texas, contains one of the largest, most active onshore gas fields in North America, stretching across 5000 square miles and having an estimated 15,870 producing wells as of 2011. Given that these operations may occur in relatively close proximity to populated/urban areas, concerns have been expressed about potential impacts on human health. In response to thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
80
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 3 publications
3
80
1
6
Order By: Relevance
“…An air sampling study conducted at a private residence in the same region by Colborn et al (2014) identified numerous chemical species that have the potential to cause detrimental health effects, such as endocrine disruptors, and detected levels of poly-aromatic hyrocarbons (PAHs) high enough to lead to diminished mental development in children who suffered prenatal exposure. Conversely, Bunch et al (2014) reported that ambient levels of NMHC air toxics in the Barnett Shale (e.g., benzene, toluene) were not present at levels that would constitute a health concern based upon both acute and chronic exposure limits, as defined by the Texas Commission on Environmental Quality (TCEQ). It should be noted, however, that exposure limits are typically determined upon exposure to individual chemicals, and do not account for effects from interactions amongst multiple chemicals, nor do they include impacts on prenatal development, such as is the case with endocrine disruptors (Colborn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An air sampling study conducted at a private residence in the same region by Colborn et al (2014) identified numerous chemical species that have the potential to cause detrimental health effects, such as endocrine disruptors, and detected levels of poly-aromatic hyrocarbons (PAHs) high enough to lead to diminished mental development in children who suffered prenatal exposure. Conversely, Bunch et al (2014) reported that ambient levels of NMHC air toxics in the Barnett Shale (e.g., benzene, toluene) were not present at levels that would constitute a health concern based upon both acute and chronic exposure limits, as defined by the Texas Commission on Environmental Quality (TCEQ). It should be noted, however, that exposure limits are typically determined upon exposure to individual chemicals, and do not account for effects from interactions amongst multiple chemicals, nor do they include impacts on prenatal development, such as is the case with endocrine disruptors (Colborn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, existing research gives support to resident reports of acute and long-term health symptoms and other reductions in quality of life. Even as they offer conflicting evidence of the relative importance of one stage of production or another to air emissions [10,11], or differ in their ultimate conclusion regarding the existence [10,11,14,35,36,39] or lack [21,40,41] of human health threats from air emissions, they find VOC concentrations in ambient air considerable distances from well pads, including in residential areas and public spaces.…”
Section: Introductionmentioning
confidence: 99%
“…They also explain why air quality studies carried out in UOG regions yield conflicting results. For example, McKenzie et al [11] found greater cumulative cancer risks and higher non-cancer hazard indices for residents living less than 0.5 miles from certain well pads in Colorado, while Bunch et al [21] analyzed data from monitors focused on regional atmospheric concentrations in the Barnett Shale region and found no exceedance of health-based comparison values. Colborn et al [10] gathered weekly, 24-hour samples 0.7 miles from a well pad in Garfield County, and noted a "great deal of variability across sampling dates in the numbers and concentrations of chemicals detected."…”
Section: Introductionmentioning
confidence: 99%
“…In this case, vociferous complaints have been raised in rural towns such as Karnes City regarding the lack of regulatory protection for residents from bad air quality allegedly due to local oil and gas activities within a few miles of their homes (Song et al, 2014). Increasingly, citizens demand accurate information on oil and gas site emissions and their public health consequences, information that remains scarce despite recent scientific attention (Petron et al, 2012;McKenzie et al, 2012McKenzie et al, , 2104Adgate et al, 2014;Bunch et al, 2014). Commonly acknowledged sources of uncertainty are the lack of sustained monitoring of ambient concentrations of pollutants associated with gas mining, poor quantification of their emissions, and inability to correlate health symptoms with specific emission events.…”
Section: Introductionmentioning
confidence: 99%